A hybrid analytical scheme for the numerical computation of time fractional computer virus propagation model and its stability analysis. (April 2020) - Dubey, Ved Prakash; Kumar, Rajnesh; Kumar, Devendra
Highlights: We examine a fractional computer virus propagation model. The fractional Routh–Hurwitz stability criterion is used to analyze the local stability of the model. The HPTM is employed to perform the numerical simulation for the model. The impact of order of Caputo fractional derivative is presented in the form of graphs. Abstract: In this paper, we present an application of the homotopy perturbation transform method to compute the approximate analytical solution of the nonlinear fractional order computer virus propagation (CVP) model. The fractional derivatives are used in Caputo sense. The proposed approximate method generates the numerical solution in the shape of a rapid convergent series by utilizing the provided initial conditions. The main purpose of the paper is to analyze the effect of variation of fractional order α on the meeting time of susceptible, infected and recovered computers. Moreover, the local stability analysis of the fractional order computer virus model is also presented using Routh–Hurwitz stability criterion.